Institutional Silence : Venezuela’s non-payment of welfare benefits in Spain - Manjarrés Ramos, Elízabeth (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
As of 2015, Venezuelan retirees and pensioners living in Spain stopped receiving their benefits and retirement pensions. In the face of this arbitrary non-payment, the only response they have received from Venezuelan institutions has been an unwavering silence. In light of this, we propose to study institutional silence and its effects. The research takes a qualitative approach and uses the ethnographic method to gather data. The conclusions sustain that institutional silence has perpetuated any potential resolution to the dispute and has hindered the implementation of other protection mechanisms for those affected, thereby promoting associationism and social protest.